Fatty liver diseases, bile acids, and FXR - Yan Zhu; Hongxia Liu; Min Zhang; Grace L. Guo (Elsevier, 2016)
The prevalence of nonalcoholic fatty liver disease (NAFLD) worldwide has increased at an alarming rate, which will likely result in enormous medical and economic burden. NAFLD presents as a spectrum of liver diseases ranging from simple steatosis, nonalcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and even to hepatocellular carcinoma (HCC). A comprehensive understanding of the mechanism(s) of NAFLD-to-NASH transition remains elusive with various genetic and environmental susceptibility factors possibly involved. An understanding of the mechanism may provide novel strategies in the prevention and treatment to NASH. Abnormal regulation of bile acid homeostasis emerges as an important mechanism to liver injury. The bile acid homeostasis is critically regulated by the farnesoid X receptor (FXR) that is activated by bile acids. FXR has been known to exert tissue-specific effects in regulating bile acid synthesis and transport. Current investigations demonstrate FXR also plays a principle role in regulating lipid metabolism and suppressing inflammation in the liver. Therefore, the future determination of the molecular mechanism by which FXR protects the liver from developing NAFLD may shed light to the prevention and treatment of NAFLD.